Seawater Batteries: An Oxygenophilic Atomic Dispersed FeNC Catalyst for Lean‐Oxygen Seawater Batteries (Adv. Energy Mater. 23/2021). Issue 23 (17th June 2021) - Meng, Rongwei; Zhang, Chen; Lu, Ziyang; Xie, Xiaoying; Liu, Yingxin; Tang, Quanjun; Li, Huan; Kong, Debin; Geng, Chuan‐Nan; Jiao, Yan; Fan, Zehui; He, Qing; et al.
Abstract : In article number 2100683, Chen Zhang, Guowei Ling, Quan‐Hong Yang and co‐workers report an oxygenophilic electrocatalyst for use in lean‐oxygen seawater in the deep sea. The double‐adsorption sites on the G/CNT interface and the high activity of Fe‐N4 active sites guarantee outstanding oxygen reduction reaction performance in seawater, enabling construction of a stable seawater battery with an ultra‐long lifespan under extremely lean‐oxygen conditions.